Public Relations in electoral campaigns - Valdez Zepeda, Andrés (2019)
The essay makes a description of the strategical role the play public relations during electoral campaigns. In the beginning, the essay conceptualizes public relations and its connection with political campaigns. It is argued that make an electoral campaign imply a public relation activity with the objective of knowing the voters and make up different political strategies to get their votes and, consequently, avoid the opposition can win the political power. It is concluded that the successful in a political campaigns depends on the creative, intelligent and innovative use of public relations.